Results of swine feeding experiments, 1946. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
In order to produce swine profitably, it is necessary to make use of forage crops. This practice will not only save grain, but will contribute to the general health of the swine themselves. Since the country has been at war, grain has not always been available. As a result, hog feeders are interested in methods of fattening that will utilize the maximum amount of pasture so that grain can be saved.
Keywords: Swine; Feeding; Protein; Grain; Pasture